AN ASSESSMENT OF THE DIFFERENT LEADERSHIP STYLES ON BUSINESS PERFORMANCE: A CASE STUDY OF TM HYPERMARKET IN BULAWAYO, ZIMBABWE (Singaporean Journal of Business Economics and Management, 2014)
This study sought to investigate the leadership styles on organisational performance at the TM Hypermarket branch in Bulawayo. The purpose of this study was concerned with analysing the effects of leadership styles on performance and establish the extent to which leadership styles are compatible with the required strategy. Finally, the research aimed to assess the effectiveness of the TM Hypermarket employee career promotional policy. The study used both quantitative and qualitative approaches. Using convenience sampling, a sample of 90 respondents were included in the study. The collected data were analysed using descriptive statistics techniques. The findings indicated that corporate leadership style was not highly practiced. Authoritative leadership dominated the organisation, especially in departmental offices, whereas participative leadership was less prevalent. Conclusions were that the lack of corporate leadership, dominating authoritative leadership style and low participative leadership style contribute to the poor performance of the organisation. Recommendations from the study were that visionary leaders and empowerment is necessary to motivate employees at TM Hypermarket in Bulawayo.